Peripapillary Vessel Density as Early Biomarker in Multiple Sclerosis - Cennamo, Gilda; Carotenuto, Antonio; Montorio, Daniela; Petracca, Maria; Moccia, Marcello; Melenzane, Antonietta; Tranfa, Fausto; Lamberti, Anna; Spiezia, Antonio L.; Servillo, Giuseppe; De Angelis, Marcello; Petruzzo, Martina; et al. (Frontiers in Neurology, 2020)
Background: To evaluate retinal vessel density (VD) in macular and in peripapillary regions in patients with recent onset of multiple sclerosis, at initial demyelinating event (IDE) and in matched relapsing-remitting multiple sclerosis (RRMS) patients. Methods: We evaluated VD in superficial capillary plexus, deep capillary plexus, choriocapillaris and radial peripapillary capillary plexus in IDE, RRMS patients and in matched healthy controls (HCs) through Optical Coherence Tomography Angiography (OCT-A). Clinical history, including history of optic neuritis, Expanded Disability Status scale and disease duration of patients were collected. Results: Thirty patients (20 with IDE and 10 with RRMS) and 15 HCs were enrolled. IDE patients showed a lower VD in radial peripapillary capillary plexus compared with controls (coeff. β = -3.578; p= 0.002). RRMS patients displayed a lower VD in both superficial capillary plexus and radial peripapillary capillary plexus compared with HCs (coeff. β = -4.955; p= 0.002, and coeff. β = -7.446; p<0.001, respectively). Furthermore, RRMS patients showed a decreased VD in radial peripapillary capillary plexus compared with IDE patients (coeff. β = -3.868; p= 0.003). Conclusions: Peripapillary region vessel density reduction, revealed through OCT-A, might be considered as an early event in MS, and might be relevant as a biomarker of disease pathology.